Looking for a Location: Dissociated Effects of Event-Related Plausibility and Verb–Argument Information on Predictive Processing in Aphasia - Hayes, Rebecca A. (Am J Speech Lang Pathol, 2016)
PURPOSE: This study examined the influence of verb–argument information and event-related plausibility on prediction of upcoming event locations in people with aphasia, as well as older and younger, neurotypical adults. It investigated how these types of information interact during anticipatory processing and how the ability to take advantage of the different types of information is affected by aphasia. METHOD: This study used a modified visual-world task to examine eye movements and offline photo selection. Twelve adults with aphasia (aged 54–82 years) as well as 44 young adults (aged 18–31 years) and 18 older adults (aged 50–71 years) participated. RESULTS: Neurotypical adults used verb argument status and plausibility information to guide both eye gaze (a measure of anticipatory processing) and image selection (a measure of ultimate interpretation). Argument status did not affect the behavior of people with aphasia in either measure. There was only limited evidence of interaction between these 2 factors in eye gaze data. CONCLUSIONS: Both event-related plausibility and verb-based argument status contributed to anticipatory processing of upcoming event locations among younger and older neurotypical adults. However, event-related likelihood had a much larger role in the performance of people with aphasia than did verb-based knowledge regarding argument structure.